Oral pemphigus vulgaris in children and adolescents: a review of the literature and a case report - A. ARIYAWARDANA, W. M. TILAKARATNE, M. DISSANAYAKE, N. VITANAARACHCHI, L. K. BASNAYAKE, M. A. M. SI (Paediatric Dentistry, 2005)
This paper describes a case of oral pemphigus vulgaris (PV) in a child that was diagnosed in its early stages and managed successfully.